Essentialism and the diasporic native informant: Malaysia in Hsu Ming Teo’s love and vertigo - Shanthini Pillai (Penerbit UKM, 2010)
Hsu Ming Teo’s (2000) novel Love and Vertigo oscillates between three countries, Singapore, Malaysia and Australia. Though Teo is seen to be affiliated with Malaysia, and certainly appraised as articulating her ethnic history with clarity of creative and artistic skill, the image of Malaysia that she shapes come to the fore as a remembered reality, through the glimpses caught from the morsels of both memory and filial visits to this estranged home/ancestral land. The most significant issue that resides at the heart of such writings is the repudiation of the Chinese community by the Malays in Malaysia. The images of Malaysia in the novel are fleeting, yet when they do appear they seem to be the most macabre amongst the spectres of the past that haunt the main protagonist, Grace. This article discusses the almost ghostly role that Malaysia plays in the novel and argues that the cultural memory of the older country lies entombed with the ghost of the 1969 racial riots. It concludes that when writings by diasporic native informants such as Teo and others around the globe are taken to be authentic renditions of ethnic heritage as part of multicultural politics in the cosmopolitan, the implications of these are highly serious as they are largely constructions of decidedly essentialist discourses of the older country.